RNA-Seq-mediated transcriptomic analysis of heat stress response in a polar Chlorella sp. (Trebouxiophyceae, Chlorophyta) - Poong, Sze Wan; Lee, Kok Keong; Lim, Phaik Eem; Pai, Tun Wen; Wong, Chiew Yen; Phang, Siew Moi; Chen, Chien Ming; Yang, Cing Han; Liu, Chun Cheng (Springer Verlag, 2018)
The current outlook on mitigation of global warming does not appear promising, with figures in the reduction of anthropogenic greenhouse gas emissions lagging far behind climate goals. A recent environmental report even postulated a high possibility of temperature increase of at least 3 °C by 2100. Despite the low number of human inhabitants in Antarctica, the Antarctic Peninsula was reported as one of the most rapidly warming locations on earth. Many studies have shown that heat stress modulates physiological performance in many species of microalgae; however, studies to elucidate the molecular mechanisms of high-temperature thermotolerance are generally focused on the model species, i.e. Chlamydomonas reinhardtii. Furthermore, previous transcriptomic work in this aspect generally employed the microarray technique and/or involved the tropical or temperate strains, and few were conducted on the polar strains. In this study, RNA-Seq-mediated transcriptomic analysis was undertaken to compare the whole transcriptome profile of an Antarctic Chlorella sp. grown at ambient (4 °C) versus stress-inducing high (33 °C) temperatures and harvested at the 120-h time point. The findings of this study indicated a coordinated response to fine tune balance between energy production and utilisation for biosynthesis by redirecting carbon provision, and the arrest of cell division as a coping mechanism for an intense and relatively long period of stress. The strategies undertaken by this alga in acclimation to heat stress are somewhat similar to the heat stress response of the model species.